Ist es notwendig, ein Heiliges Grab für die Aufführungen der Karfreitagsoratorien einzurichten? : einige Bemerkungen zur Aufführung der Karfreitagsoratorien aus der böhmischen Region - Robert Hugo (Musicologica Brunensia, 2014)
This paper summarizes the author's experience from the performances of the Good Friday oratorios at the Church of the Holy Saviour in Prague Clementinum. The Holy Sepulchre was built for the Good Friday service at this church as early as the 17th century. In the second half of the 18th century the Jesuits were giving quite a high amount of 60 Gulden for its costruction. In 2010 the church purchased a replica of the Holy Sepulchre based on a Baroque design by Andrea Pozza. The second part of the paper provides a few remarks on the instrumentation of the Good Friday oratorios. On its basis it is suggested, that the Good Friday performances in the first half of the 17th century had more of a character of public concerts with relatively little relation to the liturgy.